CONTRIBUTION OF TOPOLOGICAL DEFECTS TO THE VARIABILITY AND STRUCTURE OF EXTRAGALACTIC SOURCES OF LIGHT - Ossipov, D. L. (Одеські астрономічні публікації, 2017)
We discuss the mechanism of the fast extrinsic variability of the compact extragalactic sources of electromagnetic radiation due to the diffraction on cosmic strings. The multiple string intervention could give rise both to observable variability and considerable increase in observable luminosity of quasars. The light curves due to the intervention of strings are obtained.